Senate Resolution 15/2017: a case of unconstitutional manipulation (Revista do Tribunal Regional Federal da 3ª Região, 2017)
The senatorial power to suspend the effectiveness of normative acts is not unlimited. If there is a change in the understanding of the Constitutional Court, the Federal Senate cannot suspend the validity of norms, and should trigger the legislative process to achieve the desired end. The act that suspended articles that authorize the collection of FUNRURAL is not valid because it would require observing the regular legislative process.
Keywords: Resolution no. 15/2017; manipulation; suspension of the validity of regulations; funrural